THE EFFECT OF INTELLECTUAL CAPITAL, EARNINGS MANAGEMENT AND COMPANY AGE ON THE COMPANYS’S FINANCIAL PERFORMANCE: AS IMPLEMENTATION OF ACHIEVEMENTS SUSTAINABILITY DEVELOPMENT GOALS NO.8 - Deby Fatmah Wati; Sigit Hermawan (PT. Antis International Publisher, 2025)
Objective: This study aims to determine the effect of intellectual capital, earnings management, and company age on company financial performance (as an implementation of Sustainable Development Goal No. 8). Method: The research method used is quantitative. The population was taken from LQ45 companies listed on the IDX from 2019 to 2023. Sampling was conducted using purposive sampling. The research population consisted of 100 companies, but after passing the specified sampling criteria, only 95 companies remained. The data analysis technique used was descriptive statistical analysis, using multiple regression analysis, with the Statistical Package for Social Sciences (SPSS) Statistics version 26 software. Result: The results of the study show that Intellectual Capital and Company Age have a positive and significant effect on Financial Performance, while Profit Management has a negative and significant effect on Financial Performance. Novelty: The implications of this study are to provide additional information for investors to be more cautious in investing, and to serve as a consideration for investors in formulating investment strategies so that they can more comfortably use all of their funds to avoid losses due to financial statement phenomena and manipulation occurring in companies.